Creativity and Standardization: The Ability of Museum-Based Programming to Inform 21st Century Education | Créativité et normalisation : la capacité des programmes muséaux à renseigner l’éducation au 21ème siècle - Godfrey, Jennifer Robin; McLeod, Heather Skye (The Canadian Review of Art Education / Revue canadienne d’éducation artistique, 2017)
This paper reports the findings of an investigation of an educational programme situated in a provincial museum complex. Phase One of the research focused on teachers and showed the program promoted observation and reflection. Phase Two assessed the impact on student achievement. The data gathering method necessary for Phase Two revealed tensions between standardization and the arts community. Working with this tension, researchers defined achievement and measured essential program goals of the curriculum (“21st century competencies”). The discussion is interpretive and it is argued that museum-based experiential programming could be a contributor to the discussion on 21st century education policy.Keywords: Museum-Based Education; Standardization; 21st Century Skills; Educational AssessmentRésumé : Cet article relate les résultats d’une enquête menée sur un programme d’étude au sein d’un complexe muséal provincial. La phase un de la recherche ciblant les enseignants a démontré que le programme encourageait l’observation et la réflexion. La phase deux concernait l’impact du programme sur les réalisations des élèves. La méthode de collecte des données utilisée en phase deux a mis en évidence certaines tensions entre la normalisation et la communauté artistique. Les chercheurs ont utilisé ces tensions pour définir la réalisation et quantifier les objectifs premiers du programme (les « compétences au 21ème siècle »). Dans un contexte de discussion interprétative, on y affirme que la programmation expérientielle à caractère muséale, pourrait alimenter le débat sur la politique pédagogique au 21ème siècle.Mots-clés : éducation muséale ; normalisation ; compétences au 21ème siècle ; évaluation pédagogique